The Education in Local Islamic Culture of Maulid Nabi Tradition: a Case Study in Nurul Yaqin Ringan-Ringan Pakandangan Padang Pariaman Boarding School - Ahmad Rivauzi (AT-TA'LIM, 2015)
A wave of globalization encourages intercultural contact more rapidly. This led to  an integration between the new values with the old ones that occur outside as well as inside the organization. This encourages the fusion of process and haziness value, even the erosion of the original values of the previously sacred and the identity of a nation. This paper focus on the tradition of Maulid Nabi as one of the local Islamic traditions in Nurul Yaqin Ringan-Ringan Pakandangan Padang Pariaman Boarding School. The tradition of the Maulid Nabi (Prophet's birthday) is a particular religious practice as a result of the grounding the normative teachings of Islam into reality. Education through local Islamic culture is needed by a community in order to have resilience and ability to acquire the significance life such as found in the Nurul Yaqin Ringan-Ringan Pakandangan Pariaman Boarding School’s community. Keyword : Education, Local Islamic culture, and Warnings Birth of the ProphetCopyright © 2015 by Al-Ta'lim All right reserved